Land use segregation in measuring urban sprawl on highway strip parameters using remote GIS - Hj. Mohd. Noor, Norzailawati; Nur Aulia, Rusni (2012)
The terms urban sprawl has decades-long history in academic discourse and yet there is surprisingly no commonly agreed upon definite of what exactly constitute urban sprawl. Characterizing urban sprawl using spatial measures requires a concise definition of what constitutes sprawling urban spatial patterns. This research tend to study the measurement of defining sprawl by using Land Use Segregation Index through remote sensing and GIS approach. The IKONOS pan-sharpened and Spot-5 with 1 and 2.5 meter resolution were used and combined with GIS database to analyze the geospatial indicators using the land use segregation index. In this research, Kuantan city has been selected as a study area to examine the Land Use Segregation development based on land use pattern for year 2012. The findings shows Kuantan has identified as non-sprawling cities with result from characterization in Land Use segregation that has been tested. However, the gap between sprawl and non-sprawling was very low. It is anticipated this research will provide a new direction in sprawl nationally that address finding of sprawl at the atomic level and present a robust analytical approach for characterizing urban development in city scale at once promoting a city via GIS& Remote Sensing technology respectively.